Linezolid-based Regimens for Multidrug-resistant Tuberculosis (TB): A Systematic Review to Establish or Revise the Current Recommended Dose for TB Treatment - Bolhuis, Mathieu S; Akkerman, Onno W; Sturkenboom, Marieke G G; Ghimire, Samiksha; Srivastava, Shashikant; Gumbo, Tawanda; Alffenaar, Jan-Willem C (Clinical infectious diseases, 2018)
Linezolid has been successfully used for treatment of multidrug-resistant tuberculosis (MDR-TB). However, dose- and duration-related toxicity limit its use. Here, our aim was to search relevant pharmacokinetics (PK)/pharmacodynamics (PD) literature to identify the effective PK/PD index and to define the optimal daily dose and dosing frequency of linezolid in MDR-TB regimens. The systematic search resulted in 8 studies that met inclusion criteria. A significant PK variability was observed. Efficacy of linezolid seems to be driven by area under the concentration-time curve (AUC)/minimum inhibitory concentration (MIC). Literature is inconclusive about the preferred administration of a daily dose of 600 mg. To prevent development of drug resistance, an AUC/MIC ratio of 100 in the presence of a companion drug at relevant exposure is required. A daily dose of 600 mg seems appropriate to balance between efficacy and toxicity. Being a drug with a very narrow therapeutic window, linezolid treatment may benefit from a more personalized approach, that is, measuring actual MIC values and therapeutic drug monitoring.